A Comparative Survey on Silicon Based and Surface Acoustic Wave (SAW)-Based RFID Tags: Potentials, Challenges, and Future Directions - Suresh, K. (Institute of Electrical and Electronics Engineers Inc., 2020)
Many Automatic Identification (Auto-ID) technologies such as bar codes, magnetic stripes, Optical Character Recognition (OCR) and Electronic Article Surveillance (EAS) security tags are in existence. However, they are limited by a variety of constraints on them such as limited object rate of scan, need for Line-of-Sight (LOS) operation, very small interrogation range and poor accuracy in complex environments. Research has accordingly grown rapidly in recent years into the development of robust identification or tracking mechanisms. Radio Frequency Identification (RFID) technology using readers and RFID tags, whether passive, semi-passive or active in nature, has been deemed to be a promising candidate. Silicon based IC tags are quite popular. However, some alternative RFID technologies have also been on the rise. In particular, another special type of tag based on Surface Acoustic Wave (SAW) design also has a great potential for deployment in future identification fields due to its ruggedness against harsh conditions, metallic environments, interference, small and low cost and is being thoroughly reviewed, which is ignored in other survey papers. While other chipless RFID systems based on conductive ink, ink-tattoo and others do exist, negative aspects such as inability to survive in extreme weather, larger tag size and limited data storage capacity have severely impacted the penetration of such tags in the RFID market. Therefore, the scope of this survey article does not include chipless RFID tags. This article instead provides a comparative survey of silicon based IC and SAW based tags, which has attracted much attention from both academia and industry. The underlying characteristics, principles, advantages, and limitations of such tags are thoroughly discussed, and relevant research work followed by frequency of operation and other parameters are elaborated. This article undertakes a thorough investigation into the evolution of RFID technology and comparison into the current trend in silicon based IC and SAW based RFID tags and provides a comparison across many metrics, such as read range, tag size, tag power, availability of tag power, lifespan and more importantly, cost and security. It discusses active and passive tags under silicon based IC and SAW technology. Finally, the article reviews recent advances and provides potentials, open challenges and future research directions in such RFID tags. Â© 2013 IEEE.